Zika Virus and Guillain–Barre Syndrome: Is There Sufficient Evidence for Causality? - Leis, A. Arturo; Stokic, Dobrivoje S. (Frontiers in Neurology, 2016)
Worldwide concern over Zika virus causing Guillain-Barre syndrome (GBS) soared after recent reports that Zika-related weakness was due to GBS. A global strategic response plan was initiated with recommendations for at risk countries to prepare for GBS. This plan has major economic implications, as nations with limited resources struggle to implement costly immunotherapy. Since confirmation of causality is prerequisite to providing specific management recommendations, it is prudent to review data endorsing a GBS diagnosis. We searched PubMed for manuscripts reporting original clinical, laboratory, and electrodiagnostic data on Zika virus and GBS. Five papers met criteria; four case reports and one large case-control study (French Polynesia) that attributed 42 paralysis cases to a motor variant of GBS. Brighton criteria were reportedly used to diagnose GBS, but no differential diagnosis was presented, which violates criteria. GBS was characterized by early onset (median 6 days post-viral syndrome), rapid progression (median 6 days from onset to nadir), and atypical clinical features (52% lacked areflexia, 48% of facial palsies were unilateral). Electrodiagnostic evaluations fell short of guidelines endorsed by American Academy of Neurology. Typical anti-ganglioside antibodies in GBS motor variants were rarely present. We conclude that there is no causal relationship between Zika virus and GBS because data failed to confirm GBS and exclude other causes of paralysis. Focus should be redirected at differential diagnosis, proper use of diagnostic criteria, and electrodiagnosis that follows recommended guidelines. We also call for a moratorium on recommendations for at risk countries to prepare costly immunotherapies directed at GBS.